The Commodification of Piety: Negotiating Zuhud and Consumerist Subjectivities among Students in Modern Islamic Boarding Schools - Ratnasih Ratnasih; Aris Arif Mundayat; Yuyun Sunesti (Fikri : Jurnal Kajian Agama, Sosial dan Budaya, 2025)
Modern Islamic boarding schools (pesantren) in Indonesia have traditionally instilled the value of zuhud—simplicity and detachment from worldly materialism—as a core principle of Islamic spirituality. However, modern pesantren increasingly enroll students from upper-middle-class families, who bring exposure to consumer culture, creating a fundamental tension between religious teachings that emphasize zuhud and the pervasive influence of consumerism, which celebrates material acquisition and social status. This study examines how female students (santri) at modern pesantren navigate the tension between Islamic values of zuhud and the pressures of contemporary consumer culture. This research addresses a critical gap in understanding how young religious women actively negotiate these competing influences, rather than passively accepting either religious doctrine or consumer messages. It reveals how female students (santri) reconstruct their religious identity to create contemporary forms of religiosity relevant to modernity. Using Baudrillard's theory of consumer society and Bourdieu's theory of field, habitus, and social capital, a case study was conducted at Assalaam Modern Islamic Boarding School in Sukoharjo through in-depth interviews with 15 female students who had lived there for 3-6 years and came from upper-middle-class economic backgrounds. The findings identified three negotiation types: Minimalist-Pragmatic Students, who maintain simplicity through structured consumption; Selective Negotiator Students, who develop religious justifications to legitimize consumption; and Adaptive Consumer Students, who are highly influenced by peer groups and social media. All respondents acknowledged the influence of social media, with the Fear of Missing Out (FOMO) being the primary driver for purchasing expensive items. Brand dominance (Rabbani hijabs, Adidas, Nike, Corkcicle) creates conformity pressure. The research reveals that female students (santri) actively reconstruct religious identity to accommodate modern realities, creating contemporary zuhud—a reinterpretation of simplicity as religiously responsible consumption rather than complete material rejection. Female students (santri) are active agents constructing a blend of religious-consumer identities, creating a new form of religiosity relevant to modernity.